Antioxidative properties and proximate analysis of spent coffee ground (SCG) extracted using ultrasonic-methanol assisted technique as a potential functional food ingredient - Khairi Zainol; I. Mohd Subri; Zamri Amir Izzwan; Zamzahaila Mohd Zin; Fisal Ahmad; Hasmadi Mamat (Rynnye Lyan Resources, 2020)
Spent coffee ground (SCG) produced in tons by restaurants and cafeterias and domestic consumers is a potentially good source of natural antioxidants because it contains substantial amounts of bioactive compounds. The purpose of this study was to identify the physicochemical and antioxidant properties of three different types of spent coffee ground (SCG), namely Robusta, Arabica and Liberica extracted using ultra-sonicmethanol assisted technique. DPPH, FTC, TBA, total phenolic content (TPC) and total flavonoid content (TFC) were used to measure the antioxidant properties. Robusta SCG exhibited the highest DPPH inhibition 41.63±0.04%), FTC (60.42±0.03%) and TBA analysis (73.09±0.08%). The total phenolic compounds in the samples varied widely ranging from 18.94±0.06 to 26.23±0.86 mg GAE/g sample, with Robusta SCG showing the highest value among the three, while Arabica SCG depicted the highest amount total flavonoid content (47.62±0.05 to 56.20±0.08). A strong correlation between antioxidant activity and total phenolic content were observed in this study. Compared to Arabica and Liberica SCGs expended, Robusta SCG demonstrated a stronger beneficial effect against lipid peroxidation. This study reveals that SCGs can be regarded as a new useful source of natural antioxidant with a view to increasing the use of antioxidant synthetics by using the ingredient of agro-industrial residues in food production especially ingredients for functional food.